Stimulating the Development of Soft Skills in Software Engineering Education through Design Thinking - Marques, Anna B.; Ferreira, Bruna; Lopes, Adriana; Silva, Williamson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
The development of soft skills is essential for future software engineers since the development process requires creativity, communication and problem-solving skills. Instructors can adapt pedagogical strategies to train students' soft skills and the technical knowledge needed for the profession. Design Thinking (DT) is a methodology that promotes the production of creative and innovative software solutions. Teaching DT in Software Engineering (SE) courses can promote students with an interdisciplinary teaching practice that stimulates soft skills to understand and explore problems and design innovative software solutions. This paper presents research exploring how DT provides practical experiences and it supports the development of students' soft skills from SE courses. We proposed and developed a dynamic based on the DT phase that simulates practical situations of a software project. The students' perceptions of the dynamics were analyzed qualitatively. The results showed that the dynamics promoted practical experiences and the development of soft skills, such as problem-solving, creativity, teamwork, diversity, and critical thinking.